“CRITICAL MOMENTS” AND ENGLISH TEACHER EDUCATION IN EARLY YEARS - Cardoso Pereira Rorrato, Déborah Caroline (The ESPecialist, 2022)
In contrast to traditional methodologies for training and teaching foreign languages, different alternatives have been used, such as: decolonial pedagogy, reflective approach, critical perspectives. Focusing on critical teacher education, the objective of this study is to share the results of a project for initial teacher education who teaches English in early years, and whose principle was to develop English classes in a critical bias. At the end of a year of weekly meetings, it was possible to map the concepts (VYGOTSKY, 2007; 2008) mobilized by the participants and identify the meaning given in Critical Teaching as "Critical Moments" (PENNYCOOK, 2004). Thus, we emphasize the relevance of researches and teaching practices in the field of critical applied linguistics, which approaches the dynamism of human relations informed by language (PENNYCOOK, 2004) and the development of practices based on the lived life (RAJAGOPALAN, 2003).